Online Shop Consumer Purchasing Decision: A Study on The Significance of Self-Esteem and Marketing Mix - Tety Elida; Wahyu Rahardjo; Ari Raharjo (Jurnal Manajemen Indonesia, 2021)
The phenomenon of online shopping through various internet media broadens the scopes of studies in economics and psychology. The considerable factors which influence the purchasing decision of consumers in online shopping are the internal factors (e.g., self-esteem) and external factors (e.g., marketing mix). The aim of this study is to prove the constellation of self-esteem and marketing mix that can explain the purchasing decision of consumers in online shopping. The participants of this study are 270 online shoppers from various professions and ages. SEM is used to accomplish the objectives of the study. The findings showed that the empirical model achieved the goodness of fit which indicated that self-esteem and marketing mix had correlation with an online shopper purchasing decision. Moreover, the study found that self-esteem partially had no direct influence towards purchasing decision, yet it had a direct influence on marketing mix. On the other hand, marketing mix had a direct influence on purchasing decision. Keywords—consumer behavior; self-esteem; marketing mix; purchasing decision; online shopping